Uganda : 2017 Article IV Consultation and Eighth Review Under the Policy Support Instrument-Press Release; Staff Report; and Statement by the Executive Director for Uganda. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2017)
This 2017 Article IV Consultation highlights that Uganda's recent economic performance has been sound, notwithstanding a slowdown in growth. Real GDP growth is estimated to have slowed to 3.9 percent in FY2016/17, reflecting domestic factors and external headwinds, including the drought in the Horn of Africa. The banking sector remains well-capitalized overall. However, elevated nonperforming loans have constrained bank lending which contributed to the growth slowdown. Food price inflation increased owing to the drought, but core inflation was 5.1 percent in May 2017, in line with the Bank of Uganda's target. The outlook is broadly favorable. With steadfast policy implementation and assuming improved weather conditions, growth could accelerate to 5 percent in FY2017/18.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet